Cellular Responses Modulated by FGF-2 Adsorbed on Albumin/Heparin Layer-by-Layer Assemblies - Kumorek, Marta; Kubies, Dana; Filová, Elena; Houska, Milan; Kasoju, Naresh; Mázl Chánová, Eliška; Matějka, Roman; Krýslová, Markéta; Bačáková, Lucie; Rypáček, František (PloS one, 2015)
In a typical cell culture system, growth factors immobilized on the cell culture surfaces can serve as a reservoir of bio-signaling molecules, without the need to supplement them additionally into the culture medium. In this paper, we report on the fabrication of albumin/heparin (Alb/Hep) assemblies for controlled binding of basic fibroblast growth factor (FGF-2). The surfaces were constructed by layer-by-layer adsorption of polyelectrolytes albumin and heparin and were subsequently stabilized by covalent crosslinking with glutaraldehyde. An analysis of the surface morphology by atomic force microscopy showed that two Alb/Hep bilayers are required to cover the surface of substrate. The formation of the Alb/Hep assemblies was monitored by the surface plasmon resonance (SPR), the infrared multiinternal reflection spectroscopy (FTIR MIRS) and UV/VIS spectroscopy. The adsorption of FGF-2 on the cross-linked Alb/Hep was followed by SPR. The results revealed that FGF-2 binds to the Alb/Hep assembly in a dose and time-dependent manner up to the surface concentration of 120 ng/cm(2). The bioactivity of the adsorbed FGF-2 was assessed in experiments in vitro, using calf pulmonary arterial endothelial cells (CPAE). CPAE cells could attach and proliferate on Alb/Hep surfaces. The adsorbed FGF-2 was bioactive and stimulated both the proliferation and the differentiation of CPAE cells. The improvement was more pronounced at a lower FGF-2 surface concentration (30 ng/cm(2)) than on surfaces with a higher concentration of FGF-2 (120 ng/cm(2)).
Keywords: skot; lidé; buněčná adheze; Culture Media; fibroblastový růstový faktor 2; Fibroblast Growth Factor 2; Protein Binding; Cattle; Cell Differentiation; Microscopy, Atomic Force; buněčná diferenciace; vazba proteinů; Heparin; Animals; heparin; Humans; Cell Proliferation; mikroskopie atomárních sil; zvířata; albuminy; Cell Adhesion; Endothelial Cells; Cell Culture Techniques; endoteliální buňky; proliferace buněk; buněčné kultury; kultivační média; Albumins